Two–step fabrication of superhydrophobic surfaces with anti–adhesion. (May 2019) - Li, Jing; Du, Feng; Zhao, Yanhui; Zhao, Shicai; Yu, Huadong
Graphical abstract: Highlights: The superhydrophobic surfaces were fabricated by coupling processing. The contact angle was as high as 156.3° and the sliding angle was 4.8°. The superhydrophobic surface exhibited an excellent low adhesion property. The superhydrophobic surface had excellent self–cleaning property. Abstract: A self–cleaning property with anti–adhesion and superhydrophobicity was fabricated on aluminum alloy surface via a facile and low–cost method coupling electro–brush plating and laser processing. The surface morphology, chemical composition, wettability, anti–adhesion and self–cleaning effect were analyzed by multiple ways. The results indicated that an array of micro–scale grooves and typical hierarchical protrusion structure were covered on the surface, and the edge of the groove was covered by micro–scale sputtering particles. The special composite structures played an important role in amplifying the hydrophobic property of surface. The surface showed excellent superhydrophobic properties. The contact angle was as high as 156.3° and the sliding angle was 4.8°. The water droplet has approached onto the superhydrophobic surface and completely bounced back to the tip of the needle on the coupling surface. The adhesion between the coupling surface and the water droplet is very weakly, the surface has excellent anti–adhesion property. Through the comparative test, the composite method also has excellent low adhesion property to the polyethylene material. In this case, the low adhesion led to a rolling and self–cleaning behavior. The approach presented in this study provides a facile, low–cost and efficient method to fabricate superhydrophobic surfaces on all types of metallic materials for commercial applications.